Uji Mikrobakteri dan Iritasi Sabun Padat Rumput Laut Gracilaria Verrucosa - Nurmaida, Nurmaida; Harianti, Harianti; Widayati Putri, Tri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2023)
This study aims to determine the irritant properties of human skin to Gracilaria verrucosa solid soap preparations and organoleptic values. the method used was a pre-experimental design type one group pretestposttest and the data were described descriptively. The results showed that ALT and pH were highest in the control sample with values of 1.9 x 104 colonies/gram and 9.2, respectively. The highest organoleptic value is soap preparation without the addition of Gracilaria verrucosa with a value of 3.2 because it has an attractive appearance with a shiny clear colour. The conclusion of the results showed that the preparation of Gracilaria verrucosa solid soap with the composition of base soap, Gracilaria verrucosa, and essential oil did not irritate the skin of volunteers and organoleptically, the value of the level of Panelists' liking for Gracilaria verrucosa solid soap preparations was highest in soap preparations without the addition of Gracilaria verrucosa compared to soap preparations with the addition of Gracilaria verrucosa. soap preparations with the addition of Gracilaria verrucosa.